Embryological and pregnancy outcomes of IVF-ET in overweight/obese and normal-weight women with PCOS - Huang, Shuo; Wang, Zheng; Yang, Rui; Li, Rong; Qiao, Jie (Frontiers in Endocrinology, 2025)
IntroductionFemale obesity has been conclusively associated with compromised fertility, adverse pregnancy outcomes and higher risks of obstetric and neonatal complications. However, it remains unclear whether the adverse outcomes observed in IVF treatments among women with obesity are primarily due to obesity itself or to underlying pathologies such as PCOS. Studies investigating the impact of overweight/obesity compared to normal weight in women with PCOS have yielded inconsistent findings.MethodsWe retrospectively analyzed 4083 women with PCOS undergoing the first IVF-ET cycle with antagonist protocol. Among them, 1755 were divided into the normal weight group (18.5 g/m2 ≤ BMI < 24.0 kg/m2), 1398 into the overweight group (24.0 kg/m2 ≤ BMI < 28.0 kg/m2) and 930 into the obese group (BMI ≥ 28.0 kg/m2). The primary outcome was live birth. Other outcomes were cycle parameters, embryological, pregnancy outcomes and birth weight of newborns. We additionally investigated potential associations of maternal BMI as a continuous variable with outcomes for both linear associations and non-linear associations.ResultWomen with overweight and obese had fewer numbers of oocytes retrieved (adjusted B: -0.82 [-1.17 to -0.47] and adjusted B: -1.86 [-2.26 to -1.46], respectively), numbers of 2PN (adjusted B: -0.52 [-0.78 to -0.26] and adjusted B: -1.86 [-2.26 to -1.46]), and numbers of good-quality embryos (adjusted B: -0.34 [-0.57 to -0.12] and adjusted B: -0.88 [-1.13 to -0.62]), compared to the women with normal weight. The live birth rate was 35.7%, 30.6% and 27.2% in the normal weight group, the overweight group and obese group, respectively (adjusted OR:0.76 [0.65 to 0.89]) for overweight verse normal weight, and adjusted OR:0.64 [0.53 to 0.76)] for obese verse normal weight). There were significant associations between higher BMI and adverse outcomes. We did not observe significant non-linear associations between BMI and these outcomes.DiscussionOverweight or obese women with PCOS undergoing IVF-ET experienced lower numbers of oocytes and good quality embryos, reduced rates of live births, and higher rates of miscarriage compared to normal-weight women with PCOS.